THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK CULTURE AND MOTIVATION ON PERFORMANCE THROUGH JOB SATISFACTION IN EMPLOYEES OF EAST TANJUNGPINANG DISTRICT, TANJUNGPINANG CITY - Adha Putra, Rizki; Indrayani, Indrayani; Satriawan, Bambang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the effect of transformational leadership, work culture and motivation with job satisfaction as a mediating variable on the performance of Kelurahan employees in East Tanjungpinang sub-district, Tanjungpinang City. The hypothesis put forward is that Transformational Leadership influences Performance, Work Culture Affects Performance, Motivation influences Performance, Job Satisfaction influences Performance, Transformational Leadership influences Job Satisfaction, Work Culture Affects Job Satisfaction, Motivation influences Job Satisfaction, Transformational Leadership influences Performance Through Job Satisfaction, Work Culture influences Performance through Job Satisfaction, Motivation Affects Performance through Job Satisfaction. The sample in this study were all employees in sub-districts in the East Tanjungpinang sub-district with a total of 83 respondents. The data obtained were analyzed using data analysis techniques with the help of PLS software. The results showed that transformational leadership had a significant positive effect on performance. Work Culture has a significant positive effect on performance. Motivation has a significant positive effect on performance. Job Satisfaction influences Performance significant positive. Transformational Leadership influenceJob satisfaction Significant Positive.Work Culturesignificantly influence Job Satisfaction. Motivation has a significant positive effect on Job Satisfaction. Transformational Leadership Affects Performance mediated by Significant Positive Job Satisfaction, Work Culture Affects Performance mediated by Significant Positive Job Satisfaction. Motivation affects Performance mediated by Job Satisfaction significantly positive.